Acute Limb Ischemia: Surgical Thromboembolectomy and the Clinical Course of Arterial Revascularization at Ankle - Shin, Ha Song; Kyoung, Kyu-Hyouck; Suh, Byoung Jo; Jun, Si-Youl; Park, Jong Kwon (International Journal of Angiology, 2013)
Surgical thromboembolectomy for acute limb ischemia using Fogarty catheter is basically a blind procedure. Therefore, the complete removal of thromboemboli in all calf arteries is difficult even if completion angiography or radiological intervention is performed. The purpose of this study is to identify whether limb salvage could be achieved if at least one ankle artery was revascularized by surgical thromboembolectomy. We also observed the effectiveness of below-knee popliteal approach. Over 1 year, surgical thromboembolectomy via below-knee popliteal artery was performed on 18 acutely ischemic limbs in 14 consecutive patients. All patients were diagnosed based on clinical symptoms and computed tomography (CT) angiography. Surgical thromboembolectomy was terminated when a pulse was detected by a handheld vascular Doppler device in at least one ankle artery after closing the arteriotomy. Patients were observed during postoperative anticoagulation therapy. Of the 14 patients, 1 died and 1 underwent amputation due to the already necrotized lesion in the foot. After 1 week of anticoagulation therapy, two or more arterial pulses were detected at the ankles in all 15 limbs from the remaining 12 patients. During the 6 to 18 months of follow-up, all 15 limbs were salvaged successfully. In acute limb ischemia, successful limb salvage could be achieved by the revascularization of at least one ankle artery by surgical thromboembolectomy with concomitant anticoagulation therapy. Below-knee popliteal approach is an effective method and is worth for further study compared with other approaches.
Keywords: thromboembolectomy; angiography; intervention; anticoagulation; Doppler